2007
DOI: 10.1103/physrevlett.99.185501
|View full text |Cite
|
Sign up to set email alerts
|

Phonons in Iron: From the Bulk to an Epitaxial Monolayer

Abstract: The confinement of materials in low-dimensional structures has significant impact on propagating excitations like phonons. Using the isotope-specific 57Fe nuclear resonant vibrational spectroscopy we were able to determine elastic and thermodynamic properties of ultrathin Fe films on W(110). With decreasing thickness one observes a significant increase of the mean atomic displacement that goes along with an enhancement of vibrational modes at low energies as compared to the bulk. The analysis reveals that thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
44
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 26 publications
6
44
0
Order By: Relevance
“…(i) The decrease in intensity of high-energy modes (15 and 18 meV) was observed before in various nanoscale systems 12,13,16,19,[21][22][23][24][25] , an effect which was found to originate from phonon scattering. From the TEM study, it was concluded that a single Sn island is composed of many Sn crystallites.…”
Section: B Phonon Density Of Statesmentioning
confidence: 80%
See 2 more Smart Citations
“…(i) The decrease in intensity of high-energy modes (15 and 18 meV) was observed before in various nanoscale systems 12,13,16,19,[21][22][23][24][25] , an effect which was found to originate from phonon scattering. From the TEM study, it was concluded that a single Sn island is composed of many Sn crystallites.…”
Section: B Phonon Density Of Statesmentioning
confidence: 80%
“…The lower the Q value, the shorter the lifetime of the phonon state, and the broader the features in the phonon spectrum. For simplicity, Q is assumed to have the same average value for all phonon modes in our analysis, which has proven to be a successful method to describe phonon lifetime broadening in metallic nanostructures 13,19,60 . The aim of using the DHO model here is to provide a simple model to explain the overall changes observed in the experimental phonon spectra.…”
Section: Damped Harmonic Oscillator (Dho) Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Another source of reduction in the phonon lifetime originates from a smaller grain size. The DHO model has been used to describe size effects in metal nanostructures 29,30 . Indeed, the lifetime in nanostructures is expected to decrease due to the smaller mean-free-path induced by the smaller crystallite size.…”
Section: B Nuclear Inelastic Scatteringmentioning
confidence: 99%
“…The measurement of the PDOS under high pressures using a diamond anvil cell (DAC), where the sample size is typically less than 1 mm 2 , has been performed to study the core of the earth. [106][107][108] In addition, many important studies using the features of nuclear resonant inelastic scattering spectroscopy have been performed, e.g., on nanoparticles, [109][110][111][112][113][114] thin films, [115][116][117][118][119][120][121] quasi crystals, 122) clathrates, 123,124) superconductors, [125][126][127][128] filled skutterudites, [129][130][131][132] and glass. 133,134) The nuclear resonance scattering method can be applied to not only solids but also liquids.…”
Section: Detectormentioning
confidence: 99%